Exploring the gender gap in physics learning: conceptual understanding of magnetism among indonesian senior high school students - Basri, Nur Akhyar; Kusairi, Sentot; Sunaryono; Adam, Dian Awaluddin; Rasyid, Fauziah; Irawan, Ivan Danar Aditya (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
Students' conceptual understanding of magnetism has been extensively studied, but limited research focuses on gender-based differences. This study aims to analyze Indonesian senior high school students’ conceptual understanding of magnetism and evaluate the influence of gender. A quantitative approach was applied using a conceptual test adapted from the Magnetism Conceptual Survey (MCS), consisting of ten multiple-choice items covering key concepts. Data from 120 students (57 males and 63 females) were analyzed. The average score was 66.84, which falls into the “Good” category based on predefined scoring intervals. Statistical analysis using the Mann-Whitney test revealed no significant gender difference (p = 0.836), and the effect size was negligible (Cohen’s d ≈ 0.078), indicating the difference was not practically significant. However, some concepts were particularly challenging, such as distinguishing between electric charge and magnetic poles (37.5% correct) and understanding magnetic force (45.8% correct). These findings suggest that while students generally demonstrate a good level of understanding, conceptual difficulties persist regardless of gender. Variations in learning outcomes appear to be influenced more by cognitive and contextual factors, such as item characteristics, spatial visualization skills, and mastery of basic physics concepts, rather than gender itself. Instructional emphasis should therefore prioritize conceptual clarity in these difficult areas over gender-specific strategies.